The investigation of current condition mechanism of Al/Y2O3/p-Si Schottky barrier diodes in wide range temperature and illuminate. (February 2021) - Sevgili, Ömer; Orak, İkram
Abstract: Yttrium oxide (Y2 O3 ) powder was used as an interface layer between metal (Al) and semiconductor (p-Si). Y2 O3 powder was coated with a spin-coating method on the p-Si and the Al/Y2 O3 /p-Si Schottky Barrier Diodes (SBD) was fabricated. The electrical characteristics of the fabricated SBD were analyzed at various temperatures and compared with each other. While ΦB0 decrease from 0.931 eV to 0.211 eV, n increased from 1.63 to 10.07 with decreasing temperature ranging from 340 K to 60 K. The Richardson constant (A ⁎ ) value obtained experimentally for the Al/Y2 O3 /p-Si SBD was founded as very close to the theoretical A ⁎ value of p-Si. Photoconductivity mechanism (PM) of the Al/Y2 O3 /p-Si SBD was examined by using the photocurrent and the illuminating intensity at −1 V and it was seen that it had a nonlinear behavior. Additionally, the structural and morphologic properties of pure-Y2 O3 were analyzed by using X-Rays Diffraction (XRD), Scanning Electron Microscopy (SEM), and Raman spectroscopy (Raman). The fabricated Al/Y2 O3 /p-Si SBD can be used as a photodiode application in various electronic and optoelectronic technologies. Highlights: Yttrium oxide (Y2 O3 ) powder was characterized by using XRD, SEM and Raman spectroscopy (Raman). The electrical properties in wide range temperature and illuminate of the Al/Y2 O3 /p-Si SBD with high-κ dielectrics insulator was investigated and their photoconductivity mechanism was detailed. The fabricated the Al/Y2 O3 /p-Si SBD can be used as a photodiodes application in various optoelectronic technologies.